Bimodal antibacterial system based on quaternary ammonium silane-coupled core-shell hollow mesoporous silica. (February 2019) - Bai, Yu-ming; Mao, Jing; Li, De-xiong; Luo, Xiao-juan; Chen, Jiang; Tay, Franklin R.; Niu, Li-na
Graphical abstract: Abstract: Hollow mesoporous silica (HMS) have been extensively investigated as a biomaterial for drug delivery. The present study developed quaternary ammonium silane-grafted hollow mesoporous silica (QHMS) to create a metronidazole (MDZ) sustained delivery system, MDZ@QHMS, with bimodal, contact-kill and release-kill capability. The QHMS was assembled through a self-templating method. Metronidazole was incorporated within the QHMS core using solvent evaporation. Antibacterial activities of the MDZ@QHMS were investigated using single-species biofilms of Staphylococcus aureus (ATCC25923), Escherichia coli (ATCC25922) and Porphyromonas gingivalis (ATCC33277). The MDZ@QHMS maintained a hollow mesoporous structure and demonstrated sustained drug release and bacteridal actvity against the three bacterial strains at a concentration of 100 μg/mL or above. These nanoparticles were not relatively cytotoxic to human gingival fibroblasts when employed below 100 µg/mL. Compared with HMS, the MDZ@QHMS system at the same concentration demonstrated antibiotic-elution and contact-killing bimodal antibacterial activities. The synthesized drug carrier with sustained, bimodal antibacterial function and minimal cytotoxicity possesses potential for localized antibiotic applications. Statement of Significance: The present study develops quaternary ammonium silane-grafted hollow mesoporous silica (QHMS) to create a metronidazole (MDZ) sustained delivery system, MDZ@QHMS, with bimodal, contact-kill and release-kill capability. This system demonstrates sustained drug release and maintained a hollow mesoporous structure. The synthesized drug carrier with sustained, bimodal antibacterial function and excellent biocompatibility possesses potential for localized antibiotic applications.